HUBUNGAN PENGGUNAAN KONTRASEPSI HORMONAL DENGAN NILAI TSH DAN T4 PADA WANITA PASANGAN USIA SUBUR DI DAERAH ENDEMI GONDOK - Suryati K.; Sukati S.; Donny K.; Samsudin M.; Mucherdiyatiningsih Mucherdiyatiningsih; Sri Supadmi (Persagi, 2004)
THE RELATIONSHIP OF HORMONAL CONTRASEPTION WITH SERUM THYROID STIMULATING HORMON (TSH) AND THYROXIN (T4) OF MARRIED WOMAN IN ENDEMIC GOITER AREA.Background: Family planning program has been practiced, not only in urban but also in rural area, including remote villages in mountainous area where sometimes were also recognized as endemic goiter area. There are findings from several studies related to the effect of using hormonal contraception to the thyroid gland function. It was recomendation to study the relationship of using hormonal contraception with serum TSH and T4 of married woman. Methods: A Case control study was conducted among married woman (20-40 years old) in IDD enamic area of Sawangan Magelang district, Central Java. There groups of married women aged 20-40 years were selected of this study (38 women for each group) as follows: Group A women using contraception (pill), group B using injection and group C using non hormonal contraception (IUD, condom or sterilization). Results: The median value of serum TSH for group A and B (1,6 µU/ml), while group C were 1.7 µU/ml. The median value of serum T4 for group A, group Band C were 8,7 µg/dl, 8,3 µg/dl and 6.9 µU/ml respectively. The median value of urine excretion (UIE) for group A, group B and group C were 159 µg/L, 199 µg/L and 163 µg/L respectively. Conclutions: There were no significant differance of serum TSH among three groups. Serum T4 of group A and group B were significantly higher than that of group C.